2021
DOI: 10.3892/etm.2021.10146
|View full text |Cite
|
Sign up to set email alerts
|

Morphine enhances LPS‑induced macrophage apoptosis through a PPARγ‑dependent mechanism

Abstract: Morphine has been widely used for the treatment of pain and extensive studies have revealed a regulatory role for morphine in cell apoptosis. However, the molecular mechanisms underlying morphine-mediated apoptosis remain to be fully elucidated. The present study aimed to investigate the effects of morphine on lipopolysaccharide (LPS)-induced bone marrow-derived macrophage (BMDM) apoptosis and to determine the role of the peroxisome proliferator-activated receptor (PPAR)γ signaling pathway in this process. BMD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…During ALI, there is a prominent increase in the number of macrophages due to disruption of the alveolar vascular epithelial barrier and inflammatory recruitment [18]. Promoting activated macrophage apoptosis to reduce the activated macrophage count can accelerate the resolution of inflammation and relief of ALI [3,4]. Our results revealed that inhibiting JMJD3 can relieve the pathological performance of ALI mice as alveolar collapse and inflammatory cell infiltration accompany the remission of inflammation.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…During ALI, there is a prominent increase in the number of macrophages due to disruption of the alveolar vascular epithelial barrier and inflammatory recruitment [18]. Promoting activated macrophage apoptosis to reduce the activated macrophage count can accelerate the resolution of inflammation and relief of ALI [3,4]. Our results revealed that inhibiting JMJD3 can relieve the pathological performance of ALI mice as alveolar collapse and inflammatory cell infiltration accompany the remission of inflammation.…”
Section: Discussionmentioning
confidence: 67%
“…The apoptosis of activated macrophages is inhibited in the response to LPS stimulation [2] which aggravates the inflammatory reaction [3]. Conversely, the enhancement of LPSstimulated macrophages' apoptosis relieves acute inflammation [3,4]. When ALI is triggered, the epithelial-endothelial barrier is disrupted [5].…”
Section: Introductionmentioning
confidence: 99%
“…This difference may be due to the different physical and chemical properties of macrophages under different stimuli and the multiple pathways of volatile anesthetic regulation of macrophages. Opioid analgesics also promoted macrophage apoptosis and reduced the expression of toll-like receptor 4 (TLR4) on macrophages ( Franchi et al, 2012 ; Kim, 2018 ; Lin et al, 2021 ). Another intravenous anesthetic, ketamine, also had a significant effect on macrophage function.…”
Section: Macrophages and Anestheticmentioning
confidence: 99%
“…The majority of experiments that involved the in vivo administration of opiates, such as morphine and heroin, or the addition of MOR, KOR, and DOR agonists to cell cultures in vitro, indicate significant suppression of the immune system. Immunosuppression was reported as reduced natural killer cell activity (Shavit et al, 1986b,a;Weber and Pert, 1989;Yeager et al, 1995;Sacerdote et al, 1997;Gavériaux-Ruff et al, 1998), cytokine and chemokine production by peripheral blood mononuclear cells (Bussiere et al, 1993;Chao et al, 1993;Bonnet et al, 2008) and monocytes (Bussiere et al, 1993;Bian et al, 1995;Roy et al, 1998), T and B cell reactivity (Sacerdote et al, 1997;Govitrapong et al, 1998), phagocytic activity (Tubaro et al, 1985;Casellas et al, 1991;Rojavin et al, 1993;Szabo et al, 1993;Tomassini et al, 2004), as well the induction of macrophage apoptosis (Bhat et al, 2004;Lin et al, 2021). Additional evidence supporting the immunosuppressive role of opioid analgesics emerges from epidemiological studies showing increased prevalence of infections such as HIV, pneumonia, hepatitis and tuberculosis among opioid users (Nath et al, 2002;Quaglio et al, 2002;Roy et al, 2011;Wiese et al, 2018).…”
Section: Clinical Use Of Opioids and Immunomodulationmentioning
confidence: 99%